Biosimilar products: Definitions and registration process - SEZER, ALİ DEMİR (MARMARA UNIV, FAC PHARMACY, 2015)
With the developments in recombinant DNA and hybridoma technology, biological products are being used for the treatment of many diseases especially in irreversible diseases and improving the quality of life of patients. After the expiry of the patent of approved biologics, biosimilar products are being produced, registered and launched in markets. In scope of this review, the status of biological and bio similar products in global markets and Turkey were evaluated along with the definitions given by FDA, EMA and Turkish Drug and Medical Device Institution and explanation of the differences of biological products compared to conventional medicines and their evaluation parameters as bio similar products are not accepted as bio equivalent same as the conventional medicines.
Keywords: Biological product; biotechnological product; biosimilar product; recombinant DNA technology; EMA; FDA